RANCANGAN SISTEM VAKUM UNTUK PROSES PENGERASAN KOMPOSIT DENGAN METODE WET LAY UP DI PROGRAM STUDI TEKNIK PESAWAT UDARA - Riyan Maulana Yusuf; Ego Widoro; Djoko Herwanto (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Composite Curing process is need vacuum system to remove air bubble and heating system to decrease time of curing proses. Vacuum and heating system at composite panel curing practical at program studi teknik pesawat udara conducted separately, so need composite panel curing equipment that have integrated Vacuum and heating system. Vacuum system in this composite panel curing equipment is designed by design step including vacuum pump selection, hose selection, vacuum system design. Discussion results rate of flow of 37 L/min. With the fluid velocity of 20m/s. vacuum pump pressure of 14.5 inHg. Components required for vacuum system is a vacuum pump, vacuum regulator, vacuum gauge, nipple, vacuum bagging port, flexible Teflon hose.